Importance of C-reactive protein as an early indicator for screening of neonatal sepsis in tertiary care hospital - Dhamsaniya, Dhruvi; Parmar, Aditya; Kharadi, Hemangini; Bhadresh, Mansi; Vyas, Bhadresh (International Journal of Contemporary Pediatrics, 2025)
Background: Neonatal sepsis remains a leading cause of morbidity and mortality in newborns, especially in resource-limited settings. Early detection is crucial for improving outcomes. This prospective study evaluates the role of C-reactive protein (CRP) as an early screening marker for neonatal sepsis in a tertiary care hospital. Methods: A total of 220 newborns having risk factors and/or clinical signs of sepsis were included in the study and CRP levels were compared with blood culture results, the diagnostic gold standard. Results: CRP demonstrated high sensitivity (92.3%) and negative predictive value (NPV) (96.1%), making it reliable for ruling out sepsis. Significant associations were observed between CRP positivity and risk factors such as prematurity, respiratory distress, meconium aspiration, maternal complications, and prolonged hospital stays (p<0.05). However, its moderate specificity (58.3%) indicates that CRP should be used alongside clinical findings and blood culture for accurate diagnosis. Conclusions: CRP is a rapid, cost-effective, and sensitive screening tool that can aid in the early detection of neonatal sepsis, facilitating timely intervention and improved clinical outcomes, particularly in resource-constrained settings.